2020
DOI: 10.1101/2020.08.24.20180026
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional signatures in non-small-cell lung cancer: a systematic review and meta-analysis of sex-based differences in transcriptomic studies

Abstract: While studies have established the existence of differences in the epidemiological and clinical patterns of lung adenocarcinoma between male and female patients, we know relatively little regarding the molecular mechanisms underlying such sex-based differences. In this study, we explore said differences through a meta-analysis of transcriptomic data. We performed a meta-analysis of the functional profiling of nine public datasets that included 1,366 samples from Gene Expression Omnibus and The Cancer Genome A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 88 publications
(120 reference statements)
0
11
0
Order By: Relevance
“…Gender has been considered as an independent prognostic factor for LUAD (18). Sex-related molecular differences can influence the outcome of LUAD (25) not be avoided. Second, many variables affect the prognosis of male and female LUAD patients, including smoking and sex hormone levels, but the SEER database did not provide information on all these variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender has been considered as an independent prognostic factor for LUAD (18). Sex-related molecular differences can influence the outcome of LUAD (25) not be avoided. Second, many variables affect the prognosis of male and female LUAD patients, including smoking and sex hormone levels, but the SEER database did not provide information on all these variables.…”
Section: Discussionmentioning
confidence: 99%
“…Wheatley-Price et al (24) noted that female LUAD patients receiving platinum-based chemotherapy had more positive prognostic effects than male LUAD patients. Given the different LUAD incidence rates and prognosis between males and females, the prognosis of LUAD for men and women need to be analyzed separately (18,25). Nomograms, which are graphical models that predict the prognosis of cancer patients, have been shown to improve prognosis determinations and treatment stratifications in patients with thyroid carcinoma (26), uterine cervical carcinoma (27), colon cancer (28), and gastric carcinoma (29).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, further studies may be required to assess the effect of sex in the response to ICIs treatment. Of note, some studies have suggested that females have higher levels of immune infiltration and others have described a larger benefit from the addition of chemotherapy to ICIs in women [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous works have applied this strategy of integrating data from numerous studies to better characterise sex differences [51][52][53]. However, to our knowledge, this is the first time that a meta-analysis of transcriptomic studies in MS has been carried out, where several tissues have been evaluated with the aim of identifying sex-specific biomarkers that provide a better understanding of the molecular mechanisms in MS. As described in the introduction section, MS has a great impact on society, being the majority cause of disability not associated with accidents in the young adult population but MS causes knowledge is very limited.…”
Section: Discussionmentioning
confidence: 99%